Free vibration of composite sandwich beam with graded corrugated lattice core. (1st December 2019) - Xu, Guo-dong; Zeng, Tao; Cheng, Su; Wang, Xiao-hong; Zhang, Kun
Abstract: A continuous homogeneous theory is employed to formulate a governing equation for predicting the free vibration of the graded corrugated lattice core sandwich beam. The Rayleigh-Ritz method is adopted to solve the governing equation for various types of boundary conditions. The natural frequencies are obtained and the theoretical predictions are validated by the numerical simulations and experimental results. An auto-cutting process combined with mold-press method was used to fabricate the graded corrugated lattice core sandwich beams. Three kinds of graded corrugated lattice core sandwich beams were designed to investigate the vibration responses of the sandwich beams. The influences of the graded parameters on the natural frequencies were discussed. Numerical simulations were carried out to calculate the natural frequencies of the graded corrugated lattice core sandwich beams. The influences of face sheet thickness, core height, beam length and graded parameter on the natural frequencies of the graded corrugated lattice core sandwich beams were studied.